Proses Clearance In dan Out Terhadap Kapal Cargo di Pelabuhan Weda Halmahera Tengah Diageni PT Pelayaran Bahtera Diserindo - Titis Ari Wibowo; Agung Kwartama (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2025)
The procedures for cargo ship clearance in and out at Weda Port, Central Halmahera, managed by PT Pelayaran Bahtera Diserindo, play a vital role in ensuring efficient port operations and regulatory compliance. The clearance-in process consists of several steps that cargo ships must complete before entering the port, including document verification, health inspections, and adherence to security protocols. On the other hand, the clearance-out process involves procedures that must be completed before a ship departs, such as submitting shipping documents and undergoing cargo inspections. This study aims to examine these procedures, identify the challenges faced, and propose recommendations to enhance the efficiency and effectiveness of clearance processes at Weda Port. By utilizing the latest data and statistics, this research also emphasizes the significant role of PT Pelayaran Bahtera Diserindo in facilitating logistics operations in North Maluku. The findings are expected to provide a comprehensive understanding of the existing procedures and their impact on Indonesia's maritime industry.